Stability of Dexamethasone during Hot-Melt Extrusion of Filaments based on Eudragit® RS, Ethyl Cellulose and Polyethylene Oxide - Vanessa Domsta; Tessa Boralewski; Martin Ulbricht; Philipp Schick; Julius Krause; Anne Seidlitz (Elsevier, 2024)
Hot-melt extrusion (HME) potentially coupled with 3D printing is a promising technique for the manufacturing of dosage forms such as drug-eluting implants which might even be individually adapted to patient-specific anatomy. However, these manufacturing methods involve the risk of thermal degradation of incorporated drugs during processing. In this work, the stability of the anti-inflammatory drug dexamethasone (DEX) was studied during HME using the polymers Eudragit® RS, ethyl cellulose and polyethylene oxide. The extrusion process was performed at different temperatures. Furthermore, the influence of accelerated screw speed, the addition of the plasticizers triethyl citrate and polyethylene glycol 6000 or the addition of the antioxidants butylated hydroxytoluene and tocopherol in two concentrations were studied. The DEX recovery was analyzed by a high performance liquid chromatography method suitable for the detection of thermal degradation products. The strongest impact on the drug stability was found for the processing temperature, which was found to reduce the DEX recovery to <20% for certain processing conditions. In addition, differences between tested polymers were observed, whereas the use of additives did not result in remarkable changes in drug stability. In conclusion, suitable extrusion parameters were identified for the processing of DEX with high drug recovery rates for the tested polymers. Moreover, the importance of a suitable analysis method for drug stability during HME that is influenced by several parameters was highlighted.